Public Satisfaction with Public Services (Study at The Department of Population and Civil Registration, Semarang City) - Harsoyo; Suparno (Direktorat Riset dan Pengabdian Kepada Masyarakat, 2021)
Public service is the role of the function of the state apparatus as a publicservant, so that the position of the Government Apparatus in public services isvery strategic because it determines the extent to which the government canprovide the best possible service to the community and the extent to which thestate carries out its role properly. The level of community satisfaction withpublic services at the Semarang City Population and Civil Registration Serviceis already good. This indicates that the community is satisfied with theperformance that has been carried out by the government. In addition, everyelement of the Community Satisfaction Index assessment is all in the goodcategory, although there are three elements that are of little value amongothers, namely service time, tariff, and product specifications for service types.The three types of public services are noted by the government to improve theirperformance in the future